Analysis of Circular Economy Approach of Solid Waste Management in Aceh Tengah - Putri Marzaniar; Erma Fiani (Sanger Journal: Social, Administration and Government Review, 2024)
Aceh Tengah district, known as the Leuser region, plays an important role in preserving the environment and improving the economic welfare of the community. To address waste management issues, the researchers aimed to apply the concept of circular economy. By using a qualitative method with a scientific approach to analyse various events, obtaining indirect observation data and indirect interviews and research using triangulation techniques. This concept can be useful to encourage communities to minimize by creating products that can be repaired and have high value, thus having a positive impact on the environment and local economy. It is crucial for the private sector to play an active role in addressing the waste problem in Indonesia. The global business sector has started to utilise the circular economy approach to combat the waste problem. The circular economy focuses on the reduction, reuse, recycling and refurbishment of materials, thereby maximising the use of raw materials and improving economic well-being. Furthermore, by implementing innovative waste management practices, Aceh Tengah can generate valuable and sustainable solutions for the region, the community, and the private sector in line with the changing times